Transformative Effects of MBKM on Student Potential in Social Studies Pedagogy: A Cross-Sectional Survey of Prospective Elementary Teachers - Anwar Marasabesy; Selvi Wulandari; Santi M.J. Wahid (AL-ISHLAH: Jurnal Pendidikan, 2026)
The Merdeka Belajar–Kampus Merdeka (MBKM) policy promotes experiential learning to strengthen pre-service teachers’ professional readiness, yet evidence in elementary social studies pedagogy remains limited. This study describes the multidimensional potential of prospective elementary teachers who participated in MBKM-related activities and examines gender differences in reported potential. A cross-sectional survey was conducted with 258 fourth-semester elementary teacher education students at Universitas Khairun, Indonesia (62% female; mean age = 20.4 years). Student potential was measured using a validated 40-item, 5-point Likert questionnaire across five dimensions: cognitive, affective, social, pedagogical creativity, and independence/adaptability (Cronbach’s α = 0.912). Item validity showed acceptable item–total correlations (r = 0.421–0.591, p .001). Because the data were non-normally distributed, gender comparisons were tested using Mann–Whitney U with effect size r = Z/√N (α = .05). Overall student potential was high (M = 169.59 of 200), with independence/adaptability yielding the highest mean dimension score (M = 34.25 of 40). Female students reported higher scores than male students across all dimensions and the total score, with statistically significant differences (p = .013–.047) but small effect sizes (r = 0.12–0.15). Participants reported strong multidimensional potential within the MBKM experiential learning context, and gender differences were consistent but modest. Given the single-institution, cross-sectional design and reliance on self-report, findings indicate associative patterns and should not be interpreted as causal effects or generalized nationally.